2022
DOI: 10.1021/acsnano.2c06261
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle Array Encapsulated with Programmed DNA Hydrogels for Rapidly Sampling and Sensitively Sensing of Specific MicroRNA in Dermal Interstitial Fluid

Abstract: Author: Please verify that the changes made to improve the English still retain your original meaning.Detection of microRNA (miRNA) in dermal interstitial fluid (ISF) has emerged as clinically useful in health status monitoring. However, it remains a great challenge owing to the difficult sampling and low abundance. Here, we report a DNA hydrogel microneedles (MNs) array to realize rapid enrichment and sensitive detection of miRNA in ISF. The MNs' patch consists of methacrylate hyaluronic acid (MeHA) equipped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 51 publications
(69 reference statements)
0
24
0
Order By: Relevance
“…The mechanical strength of Microneedles@AIE PSs was tested before testing the in vivo delivery of the drug (Figure s7). The test results showed that each microneedle did not break when subjected to a mechanical force of more than 0.1 N, already exceeding the pressure of 0.058 N required for skin puncture, which means that it is mechanically strong enough to perform skin and tumor tissue puncture . Microneedles@AIE PSs were punctured and affixed to the tumor on the back of the mice, and the mice were fluorescently imaged with an in vivo image system (IVIS) 4 h later (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical strength of Microneedles@AIE PSs was tested before testing the in vivo delivery of the drug (Figure s7). The test results showed that each microneedle did not break when subjected to a mechanical force of more than 0.1 N, already exceeding the pressure of 0.058 N required for skin puncture, which means that it is mechanically strong enough to perform skin and tumor tissue puncture . Microneedles@AIE PSs were punctured and affixed to the tumor on the back of the mice, and the mice were fluorescently imaged with an in vivo image system (IVIS) 4 h later (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…The test results showed that each microneedle did not break when subjected to a mechanical force of more than 0.1 N, already exceeding the pressure of 0.058 N required for skin puncture, which means that it is mechanically strong enough to perform skin and tumor tissue puncture. 42 Microneedles@AIE PSs were punctured and affixed to the tumor on the back of the mice, and the mice were fluorescently imaged with an in vivo image system (IVIS) 4 h later (Figure 3A). The results of IVIS showed that the presence of PyTPA could be detected in the tumor 4 h after the microneedles@AIE PSs punctured the tumor (Figure 3B).…”
Section: Preparation and Characterization Of Microneedlesmentioning
confidence: 99%
“…In this work, we constructed a NP-decorated microneedle substrate that is both a SERS substrate and a substrate-supported electrospray ionization (ssESI) mass spectrometry (MS) sample prep/ionization platform. Microneedles are widely used in the field of medical diagnostic, including in vivo sample collection, , minimally invasive trans-dermal drug delivery, , and biosensing. , Additionally, microneedles have been proven to serve as promising SERS substrates for chemical sensing. , We show that the surface chemistry of microneedles plays a crucial role in the electrostatic adsorption of functional gold nanorods (Au NRs). Particularly, superhydrophobic silanization of polydimethyl hydrosiloxane (PDMS) microneedles allows for a controlled evaporation of analytes at the micrometer tip area, facilitating the adsorption of analytes within a small SERS active area.…”
Section: Introductionmentioning
confidence: 94%
“…One fascinating technique for in situ sensing is the utilization of a microneedle (MN) array patch. Such an MN with hundreds of tiny tips (50–900 μm) can physically pierce the surface layer of the skin, enabling reaching deep skin tissue areas. Recently, MN arrays showed enormous potential and had some success for simple, rapid, continuous, painless, minimally invasive monitoring of various biomarkers on both the skin surface and under the skin, including glucose, alcohol, lactate, pH, nerve agents, and glutamate. Even so, fewer attempts have been made to develop an MN-based sensor for in situ monitoring of TYR changes so far. Wang and co-workers reported an MN electrochemical sensor, in which the immobilized catechol is rapidly transformed to benzoquinone by TYR, which is detected amperometrically .…”
Section: Introductionmentioning
confidence: 99%